Uma análise gramsciniana do conceito de projeto político-pedagógico no contexto da educação lassalista - Menezes, Loiva Teresinha Soares de (2006)
The objective of this research is to perform a Gramscian analysis of the concept of the Political-Pedagogical Project in the context of Lasallist Education. Revision of literature was the methodology used in its development, based on a bibliographical and documental research, which consisted of collection of facts and a thorough and systematic analysis of the results and conclusions related to the topic. The fundamental question of the research was: According to a Gramscian reading, what is the conception of the Political-Pedagogical Project in the context of Lasallist Education? For a better comprehension, the present study has been divided into three parts. In the first part the meaning and comprehensiveness of the Political-Pedagogical Project for the Educational Institutions is explained, then the concepts, the formulation and the formation of the Political-Pedagogical Project are examined, and lastly, its function and curricular importance are examined. In the second part the contributions of Antonio Gramsci to education are analysed, emphasising his work The Intellectuals and the Organization of the Culture and the philosophy of the praxis related to politics and culture. The third part addresses the Lasallist Education, accentuating the profile of Jean Batiste de La Salle with historical aspects of his contribution to education, the basis of Lasallist Education and its identity, the contributions of Antonio Gramsci to the analysis of the Lasallist Political-Pedagogical Project, the Lasallist educational proposal in Brazil from 1907 to 2005, the Political Pedagogical Project, and finally the trends and perspectives for Lasallist Education in the 21st century are described.